Bone Marrow Mesenchymal Stromal Cells to Treat Tissue Damage in Allogeneic Stem Cell Transplant Recipients: Correlation of Biological Markers with Clinical Responses. (17th April 2014) - Yin, Fang; Battiwalla, Minoo; Ito, Sawa; Feng, Xingmin; Chinian, Fariba; Melenhorst, Jan Joseph; Koklanaris, Eleftheria; Sabatino, Marianna; Stroncek, David; Samsel, Leigh; Klotz, Jeffrey; Hensel, Nancy F.; et al.
Abstract: Bone marrow mesenchymal stromal cells (BMSCs) have been used to treat acute graft‐versus‐host disease (GVHD) and other complications following allogeneic hematopoietic stem cell transplantation (SCT). We conducted a phase I trial using third party, early passage BMSCs for patients with steroid‐refractory GVHD, tissue injury, or marrow failure following SCT to investigate safety and efficacy. To identify mechanisms of BMSC immunomodulation and tissue repair, patients were serially monitored for plasma GVHD biomarkers, cytokines, and lymphocyte phenotype. Ten subjects were infused a fixed dose of 2 × 10 6 BMSCs/kg intravenously weekly for three doses. There was no treatment‐related toxicity (primary endpoint). Eight subjects were evaluable for response at 4 weeks after the last infusion. Five of the seven patients with steroid‐refractory acute GVHD achieved a complete response, two of two patients with tissue injury (pneumomediastinum/pneumothorax) achieved resolution but there was no response in two subjects with delayed marrow failure. Rapid reductions in inflammatory cytokines were observed. Clinical responses correlated with a fall in biomarkers (Reg 3α, CK18, and Elafin) relevant for the site of GVHD or tissue injury. The GVHD complete responders survived significantly longer and had higher baseline absolute lymphocyte and central memory CD4 and CD8 counts. Cytokine changes also segregated with survival. These results confirm that BMSCs are associated with rapid clinical and biomarker responses in GVHD and tissue injury. However, BMSCs were ineffective in patients with prolonged GVHD with lower lymphocyte counts, which suggest that effective GVHD control by BMSCs requires a relatively intact immune system. Stem Cells 2014;32:1278–1288